1982
DOI: 10.1038/ki.1982.92
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry of glomerular basement membrane of the normal and diabetic human

Abstract: HGBM were isolated from kidneys of 22 diabetic patients and 32 normal control persons. All diabetic kidneys showed severe alterations of glomerulosclerosis. The amount of basement membranes isolated from diabetic kidneys was significantly higher. The HGBM preparations were individually analyzed for phosphorus, DNA, amino acids, and carbohydrates. The cystine concentration was found to be lower in the diabetic than in normal HGBM. Contrary to other reports, there was no increase in the amounts of hydroxylysine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Therefore, the increase in UAER and serum sialic acid level may indicate a coincidence between the structural alterations in the kidney, leading to albuminuria, and the possible structural alterations in renal and extrarenal tissues, leading to increased serum sialic acid concentrations. Sialic acid content in glomerular basement membrane and on erythrocytes is reduced in diabetes (7,(11)(12)(13). Thus, release or shedding of sialic acid from tissues or cell surface to circulating blood might contribute to raising the serum sialic acid level.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the increase in UAER and serum sialic acid level may indicate a coincidence between the structural alterations in the kidney, leading to albuminuria, and the possible structural alterations in renal and extrarenal tissues, leading to increased serum sialic acid concentrations. Sialic acid content in glomerular basement membrane and on erythrocytes is reduced in diabetes (7,(11)(12)(13). Thus, release or shedding of sialic acid from tissues or cell surface to circulating blood might contribute to raising the serum sialic acid level.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports showed that increased serum sialic acid concentrations were associated with atheroscleroticdisease in the nondiabetic (8,9) as well as the diabetic population (10), although tissue sialic acid concentration was reduced in diabetic patients (7,(11)(12)(13). These discrepancies are poorly understood, and little is known about the effect of the diabetes milieu per se on sialylation.…”
mentioning
confidence: 86%
“…117 Nevertheless, decreased concentrations of sialic acid in GBM have been found in diabetic patients. 118 The anionic net charge of the glomerular barrier is primarily determined by glycosaminoglycans rich in heparan sulfate. 119 ' 120 The congenital nephrotic syndrome may result from failure to develop the sulfate-rich anionic sites in the lamina rara externa of the GBM as shown by quantitative cytochemical methods from kidney biopsies examined by electron microscopy.…”
Section: Renal Hemodynamic Disturbances Elevated Grfs In Iddmmentioning
confidence: 99%
“…Although some observations have suggested increased ECM synthesis to be the major cause, this was not universally found (Fukui et al, 1992;Suzuki et al, 1997). It has been suggested that there are qualitative changes in the ECM leading to alterations in the glomerular basement membrane (GBM) proteoglycan content, thus affecting the GBM charge (Wayl et al, 1982). Others have suggested a decrease in the diabetic kidney collagenolytic activity leading to decreased ECM breakdown and tissue accumulation (Lupia et al, 1999).…”
mentioning
confidence: 99%